Psychometric properties of the Italian version of the Developmental Coordination Disorder Questionnaire (DCDQ-Italian). (January 2015) - Caravale, Barbara; Baldi, Silvia; Capone, Luca; Presaghi, Fabio; Balottin, Umberto; Zoppello, Marina
Highlights: The DCDQ-Italian is a valid and easy screening tool for motor coordination difficulties. The three factor structure of DCDQ-Italian fits with the original. Recommendations regarding cut-offs should respect age and cultural differences. Abstract: A valid tool that contributes to the diagnosis of Developmental Coordination Disorder (DCD) is represented by the Developmental Coordination Disorder Questionnaire 2007 (DCDQ'07). Recently we developed the Italian version of DCDQ (DCDQ-Italian). The aim of this study was to further analyze the psychometric properties in a sample of Italian school children aged 5–12 years and to establish cut-off scores with respect to age groups. A total of 698 parents completed the DCDQ-Italian and 45 of them repeated it after 2 weeks for test–retest reliability. One hundred and seventeen children were tested using the Movement Assessment Battery for Children. Confirmatory factor analysis supported this version to be consistent with the original. Cronbach's alpha for the total score was 0.89 and test–retest reliability was 0.88. Two-ways ANOVA for total and single subscales showed a significant main effect for age group only and not for gender. Sensitivity and specificity for our community based sample were 59% and 65% respectively, considering the cut-off scores for the 15th percentile of M-ABC and increasing when age groups were taken into account (ROC curve = 0.62). The agreement with the original was good if 15th is considered. This is the first study on the psychometric property of DCDQ in a community sample of Italian children. The DCDQ-Italian could be used as a screening tool for motor coordination difficulties in Italian children. Slight differences in cut-offs should be considered when using this version.